High-throughput single cell nucleic acid methylation sequencing method - SHEN QINGMEI; DENG ENZE; FAN XIAOYING (2025)
The invention provides a construction method of a high-throughput sequencing library. The method comprises the following steps: carrying out nucleic acid interruption in a single-tube reaction chamber by adopting transposase with a universal joint, adding the universal joint, and then carrying out at least two rounds of ligation reactions in a branched-combination combination manner to introduce different tag combinations into genome fragments of each cell, thereby obtaining a sequencing library. The homogeneity of cell transposase breaking treatment is higher, the nucleic acid tag connection process is easier to operate, the cell flux covered by single sequencing is improved, the cost is lower, and the method is compatible with a single-cell multi-omics sequencing method. 本发明提供了一种高通量的测序文库构建方法。采用通用接头的转座酶在单管反应室里进行核酸打断并加上通用的接头，随后通过分管-合并的组合方式进行至少2轮连接反应对每个细胞的基因组片段引入不同的标签组合，获得测序文库。本发明对细胞转座酶打断处理的均一性更强，核酸标签连接过程更易操作，提高了单次测序覆盖的细胞通量，成本更加低廉，还可兼容单细胞多组学测序方法。